CARDIAC MYXOMA - Yutina Himawan; Ketut Putu Yasa; Sri Maliawan (E-Jurnal Medika Udayana, 2013)
Myxoma is a benign primary tumor of the heart which is usually occurred in adult, which usually develop in the left atrium of the heart. In 1845, Cardiac Myxoma is first described by the expert. Myxoma, an endocrine neoplasm which usually begins from the endocardium of the heart it self. Generally, the shape of myxoma are round, oval with a smooth or lobulated surface. The clinical finding of myxoma is determined by it’s location, size, and mobility. Most of the patient comes with one or more from the triad of embolism, intracardiac obstruction, and associated symptoms. Until now, operation is the only treatment for cardiac myxoma.